Design, Synthesis, and Biological Evaluation of Tetra‐Substituted Thiophenes as Inhibitors of p38α MAPK. Issue 1 (11th November 2014) - Vinh, Natalie B.; Devine, Shane M.; Munoz, Lenka; Ryan, Renae M.; Wang, Bing H.; Krum, Henry; Chalmers, David K.; Simpson, Jamie S.; Scammells, Peter J.
Abstract p38α mitogen‐activated protein kinase (MAPK) plays a role in several cellular processes and consequently has been a therapeutic target in inflammatory diseases, cancer, and cardiovascular disease. A number of known p38α MAPK inhibitors contain vicinal 4‐fluorophenyl/4‐pyridyl rings connected to either a 5‐ or 6‐membered heterocycle. In this study, a small library of substituted thiophene‐based compounds bearing the vicinal 4‐fluorophenyl/4‐pyridyl rings was designed using computational docking as a visualisation tool. Compounds were synthesised and evaluated in a fluorescence polarisation binding assay. The synthesised analogues had a higher binding affinity to the active phosphorylated form of p38α MAPK than the inactive nonphosphorylated form of the protein. 4‐(2‐(4‐fluorophenyl)thiophen‐3‐yl)pyridine had a Ki value of 0.6 μm to active p38α MAPK highlighting that substitution of the core ring to a thiophene retains affinity to the enzyme and can be utilised in p38α MAPK inhibitors. This compound was further elaborated using a substituted phenyl ring in order to probe the second hydrophobic pocket. Many of these analogues exhibited low micromolar affinity to active p38α MAPK. The suppression of neonatal rat fibroblast collagen synthesis was also observed suggesting that further development of these compounds may lead to potential therapeutics having cardioprotective properties.